Efeito do grau de transformabilidade no comportamento em abrasão de Zircônias tetragonais poli cristalinas - Murray, Henara Lillian Costa (1995)
It was studied the behaviour of zirconias with different dopants used to retain the metastable tetragonal phase. This permitted the occurrence of a stress induced toughening transformation. The different transformability degrees were associated to different toughening transformation rates. The abrasive wear tests were carried out in a pin-on-disk equipment. It was observed the increasing of wear rate with the raising of normal load and abrasive size. The specimen with low transformability degree presented the worst behaviour, that was associated to its low fracture toughness. The changing of wear severity conditions conducted to an inversion of wear behaviour of the specimens with médium and high transformability degrees. The lowest wear rate was presented by the specimen with médium transformability degree, for the using of high abrasive sizes and high normal loads. This behaviour was analysed by considering the transformation rate in different abrasive wear conditions, so that the stress induced transformation could be avoided by developing of high temperatures in the abrasive contact. In this way, the higher wear rates presented by the specimen with high transformability degree, in relation to médium degree, could be due to the small influence of toughening mechanisms induced by transformation. Raising abrasive size resulted in an increasing of the friction coefficient. Correlations between wear rate and friction coefficient presented two different behaviours, characterising possible changings on transformation rates. The optical microscopy of the wear surfaces didn't presented alterations on the wear mechanisms.